"We are sacred": An intercultural and multilingual approach to understanding reproductive health literacy for Yolŋu girls and women in remote Northern Australia. (25th January 2021) - Ireland, Sarah; Maypilama, Elaine L.
Abstract: Issue Addressed: Indigenous women continue to experience reproductive health inequities. While enhancing health literacy is suggested as an approach for reducing disparities and increasing equity, there is a paucity of literature exploring Indigenous women's conceptualisation of reproductive health literacy. This paper demonstrates one approach to developing a reproductive health literacy framework for Yolŋu (Indigenous) women in a remote Northern Australian setting. Methods: Using a decolonising participatory action research approach, a senior Yolŋu researcher led interviews, group story sharing sessions, historic site visits and on‐country cultural demonstration sessions with participants on reproductive health topics. Data were collected in the participants' first language(s) and occasionally in English. Data were digitally recorded on camera, Dictaphone, video and in handwritten notes. The senior Yolŋu researcher worked with a Yolŋu interpreter to translate the data into English. Data underwent a progressive verbal relational content analysis to map and build a framework. Results: A reproductive health literacy framework that privileges Yolŋu reproductive knowledge, practices and language was successfully co‐designed. The framework was embedded in the metaphor of Pandanus mat and uses key cultural domains of Yolŋu identity as a connecting foundation to women's reproductive knowledges and ceremonial milestones. Conclusions: The framework offers a culturally responsive and multilingual approach to sensitively discuss and operationalise reproductive health literacy. The framework empowers Yolŋu cultural identities; accounts for both Yolŋu and Western medical knowledges; and honours participants' requests for "Two‐Way" learning. So What?: This research demonstrates an innovative approach to co‐designing a culturally responsive framework for reproductive health literacy in a complex and multilingual context. Such approaches offer a promising way forward for empowering Indigenous women to define reproductive health literacy and contribute to improving their reproductive health outcomes.